The Relationship Between Arm Strength and Balance and the Ability to Perform Candle Poses in Floor Gymnastics - Latuheru, Ricardo Valentino (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
This study aims to determine the relationship between arm strength and balance with the ability to do candle posture in floor gymnastics of students of SD Inpres Kassi-Kassi Makassar, Tana Toraja Regency. This research is a type of descriptive research. The population of this study is all students of SD Inpres Kassi-Kassi Makassar with a total of 60 male students who were randomly sampled. The data analysis technique used is a correlation analysis technique using the SPSS Version 11.00 system at a significant level of 95% or ? = 0.05. Based on the results of data analysis, this study concludes that: There is a significant relationship between arm strength and the ability to perform candle postures in floor gymnastics, (ro = 0.381 with a probability level of (0.000) < ? = 0.05); There was a significant relationship between balance and the ability to perform a candle posture in floor gymnastics, (ro = 0.630 with a probability of (0.000) < ? = 0.05); There was a significant relationship between arm strength and balance and the ability to do a candle pose in floor gymnastics (Ro = 0.633 with a probability level of (0.000) < ? = 0.05).